Lessons learnt from uncommon events during robotic assisted minimally invasive oesophagectomy - Pawar, Suraj B.; Bagul, Kiran G.; Nilapwar, Rishikesh D.; Bhandari, Hitesha; Pawar, Aditya S. (International Surgery Journal, 2024)
Esophagectomy is the mainstay treatment for cancer of the esophagus. Over the last two decades robotic assisted minimally invasive oesephagectomy (RAMIE) have become increasingly popular in esophageal surgery. We present a rare complication of an air leak following RAMIE. Our patient underwent a robotic assisted total esophageal mobilization, lymph node dissection transthoracically for a lower oesophageal tumour. He developed persistent air leak and needed oxygen support. Following which thoracoscopic bullectomy was done, lung was successfully re-inflated. To the authors’ knowledge, this rare complication has only handful cases reported in the medical literature; other surgeons should be made aware of this problem.